Heat stress-induced changes in skeletal muscle: Heat shock proteins and cell signaling transduction - Hisashi Naito; Toshinori Yoshihara; Ryo Kakigi; Noriko Ichinoseki-Sekine; Takamasa Tsuzuki (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Many researchers have been interested in the effects of heat stress on skeletal muscle. Recently, it has been demonstrated that heat stress on skeletal muscle results in an increase in muscle protein mass and subsequent muscle hypertrophy, and attenuation of muscle atrophy. Although the cellular mechanism remains unclear, it is thought that heat shock proteins (HSPs), which are highly conserved proteins induced by heat stress, play a major role in these phenomena. However, new insights suggest that heat stress-induced muscle hypertrophy and the prevention of muscle atrophy may be regulated not only by elevated HSP expression but also by multiple signaling pathways associated with protein synthesis and breakdown. Additionally, heat stress seems to cause various changes in other muscle functions. Although further studies are required to reveal the molecular biological mechanisms involved in the heat stress-induced changes in skeletal muscle, heat stress may be a useful tool for increasing muscle mass, attenuating disuse skeletal muscle atrophy, facilitating an early recovery from muscle damage, and improving glucose metabolism. This paper reviews studies of these effects of heat stress on skeletal muscle.